Increasing number of young unemployment due to inflation, education, and economic growth - Atik Purmiyati, Rizky Akbar Pratama, (Opción, 2020)
This study aimed to determine the effect of economic growth, inflation rates, education and minimum salaries on youth unemployment level in the region of in-industry in Indonesia simultaneously and partially from 2007 to 2015. This study used a quantitative approach in estimating econometric models. As a result, economic growth, minimum salary value, education, and inflation rate simultaneously had a significant effect on the youth unemployment level in industrial areas in Indonesia. This study concludes that there is a correlation between factors of economic growth, inflation, and education in increasing youth unemployment.